Additive‐Free Electrophoretic Deposition of Graphene Quantum Dots Thin Films. Issue 72 (12th November 2019) - Nguyen, Tam D.; Geuli, Ori; Yeo, Loo Pin; Magdassi, Shlomo; Mandler, Daniel; Tok, Alfred Iing Yoong
Abstract: The electrophoretic deposition (EPD) of graphene‐based materials on transparent substrates is highly potential for many applications. Several factors can determine the yield of the EPD process, such as applied voltage, deposition time and particularly the presence of dispersion additives (stabilisers) in the suspension solution. This study presents an additive‐free EPD of graphene quantum dot (GQD) thin films on an indium tin oxide (ITO) glass substrate and studies the deposition mechanism with the variation of the applied voltage (10–50 V) and deposition time (5–25 min). It is found that due to the small size (≈3.9 nm) and high content of deprotonated carboxylic groups, the GQDs form a stable dispersion (zeta‐potential of about −35 mV) without using additives. The GQD thin films can be deposited onto ITO with optimal surface morphology at 30 V in 5 min (surface roughness of approximately (3.1±1.3) nm). In addition, as‐fabricated GQD thin films also possess some interesting physico‐optical properties, such as a double‐peak photoluminescence at about λ =417 and 439 nm, with approximately 98 % visible transmittance. This low‐cost and eco‐friendly GQD thin film is a promising material for various applications, for example, transparent conductors, supercapacitors and heat conductive films in smart windows. Abstract : To be in the know : A graphene quantum dot (GQD) thin film on an indium tin oxide (ITO) glass substrate by additive‐free electrophoretic deposition method was fabricated. The best surface morphological properties were achieved by varying the applied potential and deposition time. The obtained film exhibited amongst others an excellent visible transparency of about 98 %.